The Optimal Dose of the Green Tea and Coffee Extracts to Suppress the Expression of PPAR-γ and C/EBP-α on Differentiated 3T3-L1 Adipocytes - Nugrahini, Nur Ida Panca; Rohman, Mohammad Saifur; Wardani, Agustin Krisna; Martati, Erryana; Chomsy, Indah Nur (Trends in Sciences, 2023)
Obesity is the excess fat content in the body caused by the expansion of white adipose tissue. This condition begins with the differentiation of adipose tissue that is known to be controlled by 2 main transcription factors, such as Peroxisome Proliferator-Activated Receptor-γ (PPAR-γ) and CCAAT Enhancer-Binding Protein-α (C/EBP-α). Their activation and collaboration are critical for developing functioning adipocytes and preserving metabolic balance in adipose tissue. Research on the benefits of natural bioactive components that regulate adipogenesis has recently become an exciting focus. Foodstuffs reported to affect this condition positively include green coffee and green tea. The primary substance in green coffee is chlorogenic acid (CGA), meanwhile in green tea is epigallocatechin gallate (EGCG). Based on medical benefit potential, the present study evaluated the dose that produced the best effect on PPAR-γ and C/EBP-α expression between single and combined doses compared to undifferentiated adipocytes (3T3-L1). 3T3-L1 were cultured and divided into negative (NEG) and positive (DIF) groups. The DIF group is obtained by induction of differentiation, then divided into seventeen therapeutic doses. At the end of therapy, cells were fixed to measure the expression of PPAR-γ and C/EBP-α using the immunocytochemistry method. The DIF group produced the highest expression of PPAR-γ and C/EBP-α. Among the single-dose group, the lowest PPAR-γ was found in C320 and C/EBP-α in the T320 group. Meanwhile, the dose with the lowest PPAR-γ and C/EBP-α expression was found in the combination of green tea and coffee (TC) 160/80 (p-value = 0.00). The findings of this study showed that a combination of green tea and coffee extracts at doses of 160/80 has the potential for anti-obesity by suppressing the differentiation of 3T3-L1 into adipocytes by reducing the expression of PPAR-γ and C/EBP-α. HIGHLIGHTS Obesity is the excess fat content in the body caused by the expansion of white adipose tissue. This condition begins with the differentiation of adipose tissue that is known to be controlled by Peroxisome Proliferator-Activated Receptor-γ (PPAR-γ) and CCAAT Enhancer-Binding Protein-α (C/EBP-α) Natural bioactive components that regulate adipogenesis in green coffee are chlorogenic acid (CGA) and epigallocatechin gallate found in green tea (EGCG). Based on this potential, the present study evaluated the dose that produced the best effect on PPARɣ and C/EBP-α protein expression between single and combined doses compared to undifferentiated adipocytes (3T3-L1) Based on this study, the differentiated group of adipocytes (DIF) produced the highest expression of PPAR-γ and C/EBP-α. Among the single dose group, which showed the lowest average value of PPARɣ was C320, and for C/EBP-α was the T320 group. Meanwhile, the dose with the lowest PPAR-γ and C/EBP-α expression came from the combination of green tea and coffee (TC) 160/80 (p-value = 0.00) So, this research shows that green tea and green coffee extract significantly affected the expression of PPAR-γ and C/EBP-α. Green tea and coffee extracts at doses of TC 160/80 have the potential for anti-obesity by suppressing the differentiation of 3T3-L1 into adipocytes by reducing the expression of PPAR-γ and C/EBP-α GRAPHICAL ABSTRACT